KINERJA PEGAWAI (ANALISIS KOMPARATIF BERDASARKAN GENDER) DI KANTOR KEMENTERIAN AGAMA KABUPATEN BONE - Rahman, Danial (Universitas Muhammadiyah Surakarta, 2019)
This research aims to analyze the comparison of male employee performance with female employee performance at Ministry of Religious Affairs Office, Bone Regency. This research is a field study with a quantitative approach through the causal comparative. Respondents in this research as many as 46 employees were taken through proportionate random sampling technique from 85 employees at the Ministry of Religion Bone Regency. The data collection technique used is a questionnaire then analyzed by using nonparametric statistics through the Wicoxon test paired samples. The results of this study indicate that the performance of employees at the Ministry of Religious Affairs Office, Bone Regency, both men and women didn?t show a significant difference. Therefore, employee performance does not have a significant difference when compared in terms of gender.